Best Answer

Unfortunately, the browser used by Answers.com for posting questions is incapable of accepting mathematical symbols. This means that we cannot see the mathematically critical parts of the question. We are, therefore unable to determine what exactly the question is about.

However, according to the remainder theorem, the remainder is the value of the cubic function when you substitute x = 2.

Q: What is the remainder when x3 9x2 x 8 is divided by x-2?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

x3-x2

(x3 + 3x2 - 2x + 7)/(x + 1) = x2 + 2x - 4 + 11/(x + 1)(multiply x + 1 by x2, and subtract the product from the dividend)1. x2(x + 1) = x3 + x22. (x3 + 3x2 - 2x + 7) - (x3 + x2) = x3 + 3x2 - 2x + 7 - x3 - x2 = 2x2 - 2x + 7(multiply x + 1 by 2x, and subtract the product from 2x2 - 2x + 7)1. 2x(x + 1) = 2x2 + 2x2. (2x2 - 2x + 7) - (2x2 + 2x) = 2x2 - 2x + 7 - 2x2 - 2x = -4x + 7(multiply x + 1 by -4, and subtract the product from -4x + 7)1. -4(x + 1) = -4x - 42. -4x + 7 - (-4x - 4) = -4x + 7 + 4x + 4 = 11(remainder)

x3+3x2+6x+1 divided by x+1 Quotient: x2+2x+4 Remaider: -3

x3 - x2 + 2x = x*(x2 - x + 2) which cannot be factored further.

x3 - x2 + x - 2 has no rational factors.

Related questions

1.6667

Dividend: 4x4-x3+17x2+11x+4 Divisor: 4x+3 Quotient: x3-x2+5x-1 Remainder: 7

(x3 + 4x2 - 3x - 12)/(x2 - 3) = x + 4(multiply x2 - 3 by x, and subtract the product from the dividend)1. x(x2 - 3) = x3 - 3x = x3 + 0x2 - 3x2. (x3 + 4x2 - 3x - 12) - (x3 + 0x2 - 3x) = x3 + 4x2 - 3x - 12 - x3 + 3x = 4x2 - 12(multiply x2 - 3 by 4, and subtract the product from 4x2 - 12)1. 4x(x - 3) = 4x2 - 12 = 4x2 - 122. (4x2 - 12) - (4x2 - 12) = 4x2 - 12 - 4x2 + 12 = 0(remainder)

If x2 and x3 are meant to represent x2 and x3, then x2 times x3 = x5 You find the product of exponent variables by adding the exponents.

x3 + 9x2 + 27x + 27 Given the numbers in the equation, we can likely bet on (x + 3) being a factor. Let's try it with artificial division: 3 * 1 = 3 9 - 3 = 6 3 * 6 = 18 27 - 18 = 9 3 * 9 = 27 27 - 27 = 0 Bingo. So let's carry it out in long division:                       x2 + 6x + 9                    _____________________ x + 3 ) x3 + 9x2 + 27x + 27                        x3 + 3x2                                        6x2 + 27x                                        6x2 + 18x                                                                9x + 27                                                                9x + 27                                                                                    0 So we have: x3 + 9x2 + 27x + 27 = (x + 3)(x2 + 6x + 9) Which we can now factor further with relative ease: = (x + 3)(x + 3)(x + 3) = (x + 3)3

x3-x2

(x3 + 3x2 - 2x + 7)/(x + 1) = x2 + 2x - 4 + 11/(x + 1)(multiply x + 1 by x2, and subtract the product from the dividend)1. x2(x + 1) = x3 + x22. (x3 + 3x2 - 2x + 7) - (x3 + x2) = x3 + 3x2 - 2x + 7 - x3 - x2 = 2x2 - 2x + 7(multiply x + 1 by 2x, and subtract the product from 2x2 - 2x + 7)1. 2x(x + 1) = 2x2 + 2x2. (2x2 - 2x + 7) - (2x2 + 2x) = 2x2 - 2x + 7 - 2x2 - 2x = -4x + 7(multiply x + 1 by -4, and subtract the product from -4x + 7)1. -4(x + 1) = -4x - 42. -4x + 7 - (-4x - 4) = -4x + 7 + 4x + 4 = 11(remainder)

(-x3 + 75x - 250) / (x + 10) = x2 - 10x - 25

x3+3x2+6x+1 divided by x+1 Quotient: x2+2x+4 Remaider: -3

x3 /12 + 16x + c

X3 X(X2) X2(X) and, X * X * X

Dividend: 4x^4 -x^2 +17x^2 +11x +4 Divisor: 4x +3 Quotient: x^3 -x^2 +5x -1 Remainder: 7